The political and military aspects of accession of Constantine the Great - Doležal, Stanislav (Masarykova univerzita v Brně, Filozofická fakulta, 2019)
The article argues that Constantine the Great, until he was recognized by Galerius, the senior Emperor of the Tetrarchy, was an usurper with no right to the imperial power, nothwithstanding his claim that his father, the Emperor Constantius I, conferred upon him the imperial title before he died. Tetrarchic principles, envisaged by Diocletian, were specifically put in place to supersede and override blood kinship. Constantine’s accession to power started as a military coup in which a military unit composed of barbarian soldiers seems to have played an important role.
Politické a vojenské aspekty nástupu Konstantina Velikého
Keywords: Constantine the Great; Roman Emperor; 4th century; tetrarchy; Konstantin Veliký; římský císař; 4. století; tetrarchie